HAMBATAN KOMUNIKASI LINTAS BUDAYA (MAHASISWA PAPUA DI SURABAYA) - Prasmi, Sri Muliani; Sumarah, Noorshanti; Danadharta, Irmasanthi (representamen, 2019)
This study aims to determine the cross-cultural communication barriers of Papuan students in Surabaya. Qualitative approach to the cluster analysis method. Six respondents were successfully recruited by purposive sampling technique. The theory used is the theory of reducing the level of uncertainty by Charles Berger et al. And Theory of cross-cultural communication barriers by William Gudykust. This study shows the results that Papuan students experience many obstacles while living in Surabaya. Language, physical, perception and culture are key barriers to information interaction and adaptation. The barriers that occur have an impact on the social life of key informants where social disparities occur on personal key informants. However, these obstacles are reduced over time because they use three strategies to reduce obstacles, namely passive, active, and interactive strategies.Keywords: communication obstacles, cross-cultural, cultural aspects.